2014
DOI: 10.7243/2056-3779-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Fetal exposure to arsenic results in hyperglycemia, hypercholesterolemia, and nonalcoholic fatty liver disease in adult mice

Abstract: Background: Exposure to arsenic is a major concern in the United States and worldwide, since this metalloid has been associated with a number of ailments, including cardiovascular and metabolic diseases. Environmental exposures to toxicants throughout fetal development have been shown to play a critical role as triggers of adult disease. Methods: This study aimed to evaluate the contribution of fetal arsenic exposure to the onset of metabolic syndrome. Swiss Webster mice were exposed to either 100 ppb sodium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…Of the toxicants tested, arsenite may have the highest potential for human health relevance, as over 140 million people worldwide are chronically exposed to arsenite via consumption of contaminated drinking water (Chowdhury et al 2006; Ravenscroft et al 2009). Although chronic arsenite exposure is associated with cancer (Gilbert-Diamond et al 2013; Karagas et al 2004; Marshall et al 2007; Yu et al 2006), and other metabolism-related pathologies (Ditzel et al 2015; Sanchez-Soria et al 2014; Shi et al 2013), the precise mechanisms underlying pathogenesis are complex, and remain poorly understood. We also demonstrate that arsenite disrupts mitochondrial energy metabolism in fusion ( fzo-1 , eat-3 )-deficient nematodes, while increasing mitochondrial function in wild-type nematodes, and has minimal effect on mitochondrial function in fission ( drp-1 )-deficient nematodes.…”
Section: Introductionmentioning
confidence: 99%
“…Of the toxicants tested, arsenite may have the highest potential for human health relevance, as over 140 million people worldwide are chronically exposed to arsenite via consumption of contaminated drinking water (Chowdhury et al 2006; Ravenscroft et al 2009). Although chronic arsenite exposure is associated with cancer (Gilbert-Diamond et al 2013; Karagas et al 2004; Marshall et al 2007; Yu et al 2006), and other metabolism-related pathologies (Ditzel et al 2015; Sanchez-Soria et al 2014; Shi et al 2013), the precise mechanisms underlying pathogenesis are complex, and remain poorly understood. We also demonstrate that arsenite disrupts mitochondrial energy metabolism in fusion ( fzo-1 , eat-3 )-deficient nematodes, while increasing mitochondrial function in wild-type nematodes, and has minimal effect on mitochondrial function in fission ( drp-1 )-deficient nematodes.…”
Section: Introductionmentioning
confidence: 99%
“…This was the first report revealing protracted developmental exposure to arsenic and cardiovascular disease in adulthood. Our group has also demonstrated that developmental exposure to 100 ppb As (III) led to adult incidence of non-alcoholic fatty liver disease (Sanchez-Soria et al, 2014). The mechanisms of arsenic-induced cardiovascular, lung, and liver diseases are not clear and the risks and biological effects associated with arsenic ingestion at lower levels commonly found in the U.S. remain ambiguous especially for in utero exposures.…”
Section: Discussionmentioning
confidence: 92%
“…These are critical developmental periods for heart, lung, and liver, potentially making the development of these organ systems susceptible to effects of arsenic. In this regard, our laboratory reported mice exposed to 100 ppb As(III) in drinking water in utero (ED 6-term) developed non-alcoholic fatty liver disease as adults (Sanchez-Soria et al, 2014). In addition, others have shown that in ApoE −/− mice, in utero drinking water exposure (ED 8-term) to 49 parts per million (ppm) arsenite resulted in an inflammatory state in the adult liver (States et al 2012) as well as increased atherosclerosis (Srivastava et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In previous research Camenisch and colleagues studied metabolic disease risk in mice exposed prenatally to low-level arsenic. 9 In those experiments, offspring of female mice that drank water containing 100 ppb sodium arsenite during pregnancy developed nonalcoholic fatty liver disease and other signs of heightened risk for metabolic syndrome, a constellation of symptoms associated with diabetes and cardiovascular disease in humans.…”
mentioning
confidence: 99%